Rice Marketing Efficiency In Sragen Regency - Amalia Nadifta Ulfa; Masyhuri Masyhuri (Agro Ekonomi, 2019)
This study is aimed to determine the channels, margins, and the level of marketing efficiency of rice in Sragen used monopoly index (MPI) and market integration. This study used primary data obtained from direct interview, and secondary data obtained from related institutions. The rice marketing channels were obtained by surveys and interviews with the snowball sampling methods. The data were analyzed using marketing channels ranging from rice mills to consumers. The results show that there are four marketing channels of rice with the most on channels 3 about 53.3%. The first channel is the shortest channel with the lowest marketing margin, but it is inapporopiate to conclude that the first channel is the most efficient channel. The highest marketing margin of rice marketing channels is at the medium/large rice mills, while the lowest is at the wholesalers. The MPI value of collecting traders is 2.00; 2.32 for medium/large rice mills; wholesalers is 1.47; and 1.75 for retailers. The comparison of MPI in each marketing institution shows that medium/large rice mill dominate rice marketing in Sragen. The correlation analysis of 0.952 means a “very strong” correlation between price at rice mills level and price at consumers level. Based on the marketing efficiency analysis using MPI and market integration, it shows that marketing of rice in Sragen has been integrated and efficient. The research recommends further analysis of rice marketing in other areas for rice marketing for rice mills or rice traders in Sragen.